Garnet type oxide solid electrolyte, preparation method and lithium ion battery
By introducing a variety of doping elements at the Li site of the garnet-type oxide solid electrolyte, adjusting the stoichiometric number of Li, the problem of low conductivity of the existing electrolyte Li+ is solved, and higher conductivity and density are achieved.
Patent Information
- Application Number
- CN202510358975.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing garnet-type oxide solid electrolyte Li+ has a low conductivity, making it difficult to meet the performance requirements of lithium-ion batteries at room temperature.
By introducing doped elements such as Fe, B, Be, Ga, Al, Zn, etc. at the Li site, the stoichiometric number of Li is adjusted between 6.4 and 6.6, and a solid oxide electrolyte of Li (6.4~6.6)MLa3Zr2O12 type is prepared.
The Li+ conductivity of the garnet oxide solid electrolyte is significantly improved, reaching about 0.9 mS/cm, exceeding the expected effect, and improving the density and phase stability of the electrolyte.
Smart Images

Figure CN119859057A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a garnet-type oxide solid electrolyte and a preparation method, and a lithium-ion battery. Background Art
[0002] At present, lithium-ion batteries have attracted widespread attention from various energy storage systems due to their high voltage, high specific capacity, green and pollution-free characteristics. The development of new energy vehicles has also put forward higher requirements for lithium-ion batteries. Lithium-ion batteries with higher energy density, longer service life and higher safety have become the key to the technological innovation of new energy vehicles. Traditional lithium-ion batteries use organic electrolytes, which are flammable and easy to leak, which can lead to safety accidents. Solid-state lithium metal batteries that use non-flammable solid electrolytes instead of organic electrolytes and directly match lithium metal negative electrodes have broad prospects.
[0003] The core of solid-state batteries is solid electrolytes, which are mainly divided into organic, inorganic and composite solid electrolytes. Among them, inorganic solid electrolytes mainly include oxides, sulfides, halides and various new lithium ion conductors. Garnet-type Li7La3Zr2O 12 Solid-state electrolyte (LLZO) is a typical oxide solid-state electrolyte with many advantages such as high ionic conductivity, wide electrochemical window, and stability to lithium metal anode.
[0004] Li + Conductivity is an important parameter for evaluating the performance of solid electrolytes. Therefore, how to improve the Li + Conductivity is one of the key issues in the study of LLZO. A lot of research has been done on the doping of LLZO, but the existing doping schemes are not ideal for improving the ionic conductivity of LLZO. Summary of the invention
[0005] In view of this, the present application provides a garnet oxide solid electrolyte and a preparation method, and a lithium-ion battery, aiming to improve the existing solid electrolyte with Li + The problem of low conductivity.
[0006] In a first aspect, the present invention provides a garnet-type oxide solid electrolyte, wherein the chemical formula of the oxide solid electrolyte is Li (6.4~6.6) MLa3Zr2O 12 ; Wherein, M is a doping element, M includes at least two elements of Fe, B, Be, Ga, Al, and Zn, and the molar amount of each element in M is greater than 0 and less than or equal to 0.1.
[0007] In some embodiments of the present application, M includes at least three elements of Fe, B, Be, Ga, Al, and Zn; and / or, The elements in M are in equal molar ratios.
[0008] In some embodiments of the present application, M is selected from at least four elements of Fe, B, Be, Ga, Al, and Zn; or, M includes Ga, Al, Zn, Be; or, M includes Ga, Fe, Al, and B; or, M includes Ga, Fe, Al, Be, and Zn.
[0009] In some embodiments of the present application, the chemical formula of the oxide solid electrolyte is Li 6.4 Ga 0.1 Al 0.1 La3Zr2O 12、 Li 6.6 Ga 0.05 Al 0.05 Zn 0.05 La3Zr2O 12、 Li 6.5 Ga 0.05 Al 0.05 Zn 0.05 Be 0.05 La3Zr2O 12 , Li 6.4 Ga 0.05 Fe 0.05 Al 0.05 B 0.05 La3Zr2O 12 , Li 6.48 Ga 0.04 Fe 0.04 Al 0.04 Be 0.04 Zn 0.04 La3Zr2O 12 At least one of .
[0010] In some embodiments of the present application, the molar amount of each element in M is 0.03 to 0.06.
[0011] On the other hand, the present application provides a method for preparing an oxide solid electrolyte material, the preparation method comprising the following steps: Weigh a lithium source, a lanthanum source, a zirconium source and a dopant according to a stoichiometric ratio, wherein the dopant includes doping elements Fe, B, Be, Ga, Al and Zn; ball milling a mixture consisting of the lithium source, the lanthanum source, the zirconium source, the dopant and the solvent to obtain a slurry; The dried slurry is calcined at 900°C-950°C for 6h-12h, and then ground to obtain powder; Pressing the powder into a tablet and sintering at a pressure of 10 MPa to 20 MPa and a temperature of 1000° C. to 1200° C. for 1 h to 2 h to obtain an oxide solid electrolyte; Wherein, the chemical formula of the oxide solid electrolyte is Li (6.4~6.6) MLa3Zr2O 12 ; M includes at least two elements of Fe, B, Be, Ga, Al, and Zn, and the molar amount of each element in M is greater than 0 and less than or equal to 0.1.
[0012] In some embodiments of the present application, the sum of the masses of the lithium source, the lanthanum source, the zirconium source and the dopant is M1, the mass of the ball milling beads is M2, and the mass of the solvent is M3, then M1: M2: M3 is (1-5): (1-5): (5-20).
[0013] In some embodiments of the present application, the ball milling speed during the ball milling process is 250r / min-400r / min; and / or, The ball milling time in the ball milling process is 6h-12h.
[0014] In some embodiments of the present application, the process of drying the slurry comprises placing the slurry in a forced air drying oven at 80° C. to 120° C. for 6 h to 12 h; and / or, Before the sintering step, the preparation method further comprises sieving the milled particles through 200 mesh, 400 mesh, and 500 mesh sieves in sequence to obtain the powder; and / or, Before the sintering step, the preparation method further comprises dry pressing the powder to obtain a precursor, and then hot pressing and sintering the precursor to obtain the oxide solid electrolyte.
[0015] The present application also provides a lithium-ion battery, which includes the oxide solid electrolyte or the oxide solid electrolyte prepared by the preparation method.
[0016] Beneficial effects: In the present application, at least two elements of Fe, B, Be, Ga, Al, and Zn are doped with equal molar numbers on the Li site, and the stoichiometric number of Li is between 6.4 and 6.6, so that the garnet-type oxide solid electrolyte in the present application has a high Li + Conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 is the XRD spectrum of the oxide solid electrolyte prepared in Example 1 of the present application; Figure 2 is a scanning electron microscope image of the oxide solid electrolyte prepared in Example 1 of the present application; Figure 3 is the XRD spectrum of the oxide solid electrolyte prepared in Example 2 of the present application; Figure 4 is the XRD spectrum of the oxide solid electrolyte prepared in Example 3 of the present application; Figure 5 is the XRD spectrum of the oxide solid electrolyte prepared in Example 4 of the present application; Figure 6 is the XRD spectrum of the oxide solid electrolyte prepared in Example 5 of the present application; Figure 7 It is the XRD spectrum of the oxide solid electrolyte prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0019] The experimental examples described in this application are only part of the embodiments of this application, not all of the embodiments. All other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain this application, and are not used to limit this application.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0021] In the description of this application, the term "including" means "including but not limited to." The terms first, second, third, etc. are used merely as labels and do not impose numerical requirements or establish a sequence.
[0022] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0023] In this application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0024] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0025] At present, lithium-ion batteries have attracted widespread attention from various energy storage systems due to their high voltage, high specific capacity, green and pollution-free characteristics. The development of new energy vehicles has also put forward higher requirements for lithium-ion batteries. Lithium-ion batteries with higher energy density, longer service life and higher safety have become the key to the technological innovation of new energy vehicles. Traditional lithium-ion batteries use organic electrolytes, which are flammable and easy to leak, which may lead to safety accidents. Solid-state lithium metal batteries that use non-flammable solid electrolytes instead of organic electrolytes and directly match lithium metal negative electrodes have broad prospects.
[0026] The core of solid-state batteries is solid electrolytes, which are mainly divided into organic, inorganic and composite solid electrolytes. Among them, inorganic solid electrolytes mainly include oxides, sulfides, halides and various new lithium ion conductors. Garnet-type Li7La3Zr2O 12 Solid-state electrolyte (LLZO) is a typical oxide solid-state electrolyte with many advantages such as high ionic conductivity, wide electrochemical window, and stability to lithium metal anode.
[0027] Li + Conductivity is an important parameter for evaluating the performance of solid electrolytes. Therefore, how to improve the Li + Conductivity is one of the key issues in the study of LLZO. A lot of research has been done on the doping of LLZO, but the existing doping schemes are not ideal for improving the ionic conductivity of LLZO.
[0028] In view of this, the present application provides a garnet-type oxide solid electrolyte, which has high ionic conductivity.
[0029] The chemical formula of the oxide solid electrolyte provided in the embodiment of the present application is Li (6.4~6.6) MLa3Zr2O 12 ; Wherein, M is a doping element, M includes at least two elements of Fe, B, Be, Ga, Al, and Zn, and the molar amount of each element in M is greater than 0 and less than or equal to 0.1.
[0030] Taking M including two of the elements as an example, illustratively, M may include at least one of Fe and B, Fe and Be, Fe and Ga, Fe and Al, Fe and Zn, B and Be, B and Ga, B and Al, B and Zn, Be and Ga, Be and Al, Be and Zn, Ga and Al, Ga and Zn, and Al and Zn. Of course, in some embodiments of the present application, in addition to including two elements of Fe, B, Be, Ga, Al, and Zn, M may also include other elements (other doping elements except Fe, B, Be, Ga, Al, and Zn), which is not limited here.
[0031] Taking M including three of the elements as an example, illustratively, M may include Fe, B and Be; or, M may include Fe, B and Ga; or, M may include Fe, B and Al; or, M may include Fe, B and Zn; or, M may include Fe, Be and Ga; or, M may include Fe, Be and Al; or, M may include Fe, Be and Zn; or, M may include Fe, Ga and Al; or, M may include Fe, Ga and Zn; or, M may include B, Be and Ga; or, M may include B, Be and Al; or, M may include B, Be and Zn; or, M may include Be, Ga and Al; or, M may include Be, Ga and Zn; or, M may include Ga, Al and Zn. Of course, in some embodiments of the present application, in addition to including the three elements of Fe, B, Be, Ga, Al and Zn, M may also include other elements (other doping elements except Fe, B, Be, Ga, Al and Zn), which are not limited here.
[0032] For example, taking M including four elements as an example, in one embodiment, M may include Fe, B, Be and Ga. In another exemplary embodiment, M may include B, Be, Ga and Al. In another exemplary embodiment, M may include B, Be, Ga and Al.
[0033] In another exemplary embodiment, M may include four elements, Fe, Be, Al, and Zn. Of course, in some embodiments of the present application, M may include other elements in addition to at least four elements of Fe, B, Be, Ga, Al, and Zn, which are not limited here.
[0034] Exemplarily, taking M including five elements as an example, in one exemplary embodiment, M may include the five elements of Fe, B, Be, Ga, and Al. In another exemplary embodiment, the five elements of B, Be, Ga, Al, and Zn. In another exemplary embodiment, the five elements of B, Be, Ga, Al, and Zn. Of course, in some embodiments of the present application, M may include other elements in addition to at least four elements of Fe, B, Be, Ga, Al, and Zn, which are not limited here.
[0035] Of course, M may also include six of these elements. For example, M includes Fe, B, Be, Ga, Al, and Zn. Of course, in some embodiments of the present application, M may include other elements in addition to the six elements of Fe, B, Be, Ga, Al, and Zn, which are not limited here.
[0036] Exemplarily, the stoichiometric number of Li can be 6.4, 6.45, 6.5, 6.55, 6.6 and the interval between any two of the above values. It should be emphasized that in the present application, by introducing the doping element M at the Li position, the stoichiometric number of Li in the present application is below 7, and a stable cubic phase solid electrolyte can be obtained. At the same time, in the present application, the Li site is doped with at least four elements of Fe, B, Be, Ga, Al, and Zn, and the stoichiometric number of Li is between 6.4 and 6.6, so that the garnet-type oxide solid electrolyte in the present application has a higher Li + Conductivity.
[0037] Illustratively, the molar amount of each element in M can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, and intervals between any two of the above values.
[0038] It should be noted that the related art discloses single doping at the Li, La, and Zr sites, as well as dual doping and multi-doping at multiple sites of the Li, La, and Zr sites. The doping elements at the Zr site of LLZO are usually some relatively expensive rare earth elements, and the ionic conductivity is easily affected by the radius of the doped cation; and the improvement of ionic conductivity by La doping is far less than that of Li and Zr sites. Li doping improves the ionic conductivity of LLZO by directly adjusting the lithium concentration and increasing lithium vacancies, and the doping elements are usually relatively cheap. The Li of the garnet oxide solid electrolyte provided in the present application is + The conductivity can reach about 0.9mS / cm, which is much better than that of the Li-doped solution. + The conductivity was increased by more than 1 times, which was an effect beyond expectations.
[0039] It should be emphasized that the Li-doping elements in this application include Fe, B, Be, Ga, Al, and Zn, which are consistent with the first-principles calculations and have ionic radii similar to Li. This is conducive to improving the ionic conductivity of the oxide solid electrolyte in this application.
[0040] In addition, the stoichiometric number of Li in this application is between 6.4 and 6.6. The inventors have found that the stoichiometric number of Li affects the disorder of Li and Li + Transmission space, when the stoichiometric number of Li is between 6.4 and 6.6, is beneficial to improving the ionic conductivity of the oxide solid electrolyte in the present application.
[0041] In some embodiments of the present application, M is selected from at least four of Fe, B, Be, Ga, Al, and Zn, and each element in M is in an equal molar ratio. For example, M is selected from four elements, five elements, or six elements of Fe, B, Be, Ga, Al, and Zn. In this way, a high entropy LLZO solid electrolyte material can be prepared, which is beneficial to further improve the ionic conductivity of the oxide solid electrolyte in the present application.
[0042] It should be noted that the equimolar ratio of each element in M means that the doping amount of each element in M at the Li position is the same. For example, M includes four elements, Fe, B, Be and Ga. The molar content of Fe, B, Be and Ga in M is the same. For example, M is Fe 0.05 B 0.05 Be 0.05 Ga 0.05。
[0043] In some embodiments of the present application, the molar amount of each element in M is 0.03 to 0.06. Exemplarily, the molar amount of each element in M is 0.03, 0.04, 0.05, 0.06, and a value between any two of the above values.
[0044] In some embodiments of the present application, the chemical formula of the oxide solid electrolyte is Li 6.4 Ga 0.1 Al 0.1 La3Zr2O 12、 Li 6.6 Ga 0.05 Al 0.05 Zn 0.05 La3Zr2O 12、 Li 6.5 Ga 0.05 Al 0.05 Zn 0.05 Be 0.05 La3Zr2O 12 , Li 6.4 Ga 0.05 Fe 0.05 Al 0.05 B 0.05 La3Zr2O 12 , Li 6.48 Ga 0.04 Fe 0.04 Al 0.04 Be 0.04 Zn 0.04 La3Zr2O 12 At least one of .
[0045] On the other hand, the present application provides a method for preparing an oxide solid electrolyte material, the preparation method comprising the following steps: S10 A lithium source, a lanthanum source, a zirconium source and a dopant are weighed according to a stoichiometric ratio. The dopant includes doping elements Fe, B, Be, Ga, Al and Zn.
[0046] Exemplarily, the lithium salt may be lithium carbonate. The lanthanum source may be lanthanum oxide. The zirconium source may be zirconium oxide. Taking the doping elements as Ga, Al, Zn and Be as an example, the doping agent includes gallium oxide, aluminum oxide, zinc oxide and beryllium oxide. Further, according to the stoichiometric ratio calculation, the amount of lithium salt added is about 10% in excess.
[0047] S20 ball milling a mixture consisting of the lithium source, the lanthanum source, the zirconium source, the dopant and the solvent to obtain a slurry.
[0048] In some embodiments of the present application, the sum of the masses of the lithium source, the lanthanum source, the zirconium source and the dopant is M1, the mass of the ball milling beads is M2, and the mass of the solvent is M3, then M1: M2: M3 is (1-5): (1-5): (5-20).
[0049] Exemplarily, M1 can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, or a value between any two of the above values.
[0050] Exemplarily, M2 can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, and a value between any two of the above values.
[0051] Exemplarily, M3 can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 and any value between any two of the above values. Exemplarily, the solvent can be isopropanol. The mass ratio of the powder (i.e., the powder formed by the lithium source, the lanthanum source, the zirconium source and the dopant) to the zirconium oxide ball milling beads and the solvent is 1:1:10.
[0052] Exemplarily, the ball milling speed in the ball milling process is 250 r / min-400 r / min, and the ball milling time in the ball milling process is 6 h-12 h. Specifically, the ball milling speed is 250 r / min, and the ball milling time is 12 h to obtain a slurry.
[0053] S30 The dried slurry is calcined at 900° C.-950° C. for 6 h-12 h, and then ground to obtain powder.
[0054] Exemplarily, the slurry after ball milling in step S20 is placed in an 80°C-120°C forced air drying oven for 6h-12h to obtain a powder, and then the powder is placed in an alumina crucible and calcined in a muffle furnace at a heating rate of 5°C / min, a calcination temperature of 900°C, and a calcination time of 12h before cooling to room temperature. The calcined powder is then taken out, ground with a mortar, and sieved with 200 mesh, 400 mesh, and 500 mesh sieves in turn to obtain a fine and uniform powder.
[0055] S40 Sintering the powder at a pressure of 10 MPa-20 MPa and a temperature of 1000° C.-1200° C. for 1 h-2 h to obtain an oxide solid electrolyte; wherein the chemical formula of the oxide solid electrolyte is Li (6.4~6.6) MLa3Zr2O 12 ; M includes at least two elements of Fe, B, Be, Ga, Al, and Zn, and the molar amount of each element in M is greater than 0 and less than or equal to 0.1.
[0056] Exemplarily, the powder obtained in step S30 is weighed and placed in a graphite mold for dry pressing, and then transferred to a hot press furnace filled with Ar, sintered at 1000°C for 1 hour, with a pressurizing pressure of 10 MPa and a heating rate of 3°C / min. After sintering, it is slowly cooled to room temperature at a rate of 2°C / min to obtain an oxide solid electrolyte.
[0057] The technology in this embodiment adopts a hot pressing sintering method with pressing and firing, which has a shorter sintering time and a lower sintering temperature than ordinary pressureless sintering, which is beneficial to reducing energy consumption. At the same time, the density and ion conductivity of the electrolyte are also significantly improved.
[0058] Furthermore, M is selected from at least four elements of Fe, B, Be, Ga, Al, and Zn. It should be noted that in this embodiment, the doping element M is relatively large, and the use of hot pressing sintering can effectively control the steam changes of the high-pressure component system, avoiding the problem of easy generation of impurities due to numerous components in the traditional solid-phase sintering at normal pressure, and better obtains high-entropy LLZO solid electrolyte materials with higher density and ionic conductivity. In some embodiments of the present application, the sum of the masses of the lithium source, the lanthanum source, the zirconium source, and the dopant is M1, the mass of the ball milling beads is M2, and the mass of the solvent is M3, then M1: M2: M3 is 1:1:10. In some embodiments of the present application, the ball milling speed during the ball milling process is 250r / min; and / or, The ball milling time in the ball milling process is 12 hours.
[0059] In some embodiments of the present application, the process of drying the slurry comprises placing the slurry in a forced air drying oven at 120° C. for 6 hours; and / or, Before the sintering step, the preparation method further comprises sieving the milled particles through 200 mesh, 400 mesh, and 500 mesh sieves in sequence to obtain the powder; and / or, Before the sintering step, the preparation method further comprises dry pressing the powder to obtain a precursor, and then hot pressing and sintering the precursor to obtain the oxide solid electrolyte.
[0060] The present application also provides a lithium-ion battery, which includes the oxide solid electrolyte or the oxide solid electrolyte prepared by the preparation method.
[0061] Example 1: Li 6.5 Ga 0.05 Al 0.05 Zn 0.05 Be 0.05 La3Zr2O 12 Preparation.
[0062] (1) According to the stoichiometric ratio, lithium carbonate (10% excess), gallium oxide, aluminum oxide, zinc oxide, beryllium oxide, lanthanum oxide, and zirconium oxide were weighed respectively, placed in a zirconium oxide ball mill, and ball milled using isopropanol as a solvent. The mass ratio of powder to zirconium oxide ball milling beads and solvent was 1:1:10, the ball milling speed was 250 r / min, and the ball milling time was 12 h.
[0063] (2) The ball-milled powder slurry was placed in a 120°C forced air drying oven for 6 h to dry.
[0064] (3) The dried powder was placed in an alumina crucible and calcined in a muffle furnace at a temperature of 900 °C for 12 h at a heating rate of 5 °C / min.
[0065] (4) The calcined powder is ground with a mortar and sieved with 200 mesh, 400 mesh, and 500 mesh sieves in turn. The purpose of sieving is to obtain fine and uniform powder particles. Weigh 150g of the sieved powder and place it in a graphite mold for dry pressing. Then transfer it to a hot press furnace filled with Ar and sinter it at 1000℃ for 1h. The pressure is 10MPa and the heating rate is 3℃ / min. After sintering, it is slowly cooled to room temperature at a rate of 2℃ / min. The sintered electrolyte sheet is cut and processed according to the needs to obtain the final required 5mm×5mm×1mm square ceramic sheet. Its XRD spectrum is as follows Figure 1 As shown in the scanning electron microscope photos Figure 2 shown.
[0066] Example 2: Li 6.4 Ga 0.05 Fe 0.05 Al 0.05 B 0.05 La3Zr2O 12 Preparation.
[0067] (1) According to the stoichiometric ratio, lithium carbonate (10% excess), gallium oxide, aluminum oxide, iron oxide, boron oxide, lanthanum oxide, and zirconium oxide were weighed respectively, placed in a zirconium oxide ball mill, and ball milled using isopropanol as a solvent. The mass ratio of powder to zirconium oxide ball milling beads and solvent was 1:1:10, the ball milling speed was 250 r / min, and the ball milling time was 12 h; (2) drying the ball-milled powder slurry in a 120° C. forced air drying oven for 6 h; (3) The dried powder was placed in an alumina crucible and calcined in a muffle furnace at a temperature of 900 °C for 12 h at a heating rate of 5 °C / min.
[0068] (4) The calcined powder is ground with a mortar and sieved with 200 mesh, 400 mesh, and 500 mesh sieves in turn. The purpose of sieving is to obtain fine and uniform powder particles. Weigh 150g of the sieved powder and place it in a graphite mold for dry pressing. Then transfer it to a hot press furnace filled with Ar and sinter it at 1000℃ for 1h. The pressure is 10MPa and the heating rate is 3℃ / min. After sintering, it is slowly cooled to room temperature at a rate of 2℃ / min. The sintered electrolyte sheet is cut and processed according to the needs to obtain the final required 5mm×5mm×1mm square ceramic sheet. Its XRD spectrum is as follows Figure 3 shown.
[0069] Example 3: Li 6.48 Ga 0.04 Fe 0.04 Al 0.04 Be 0.04 Zn 0.04 La3Zr2O 12 Preparation.
[0070] (1) According to the stoichiometric ratio, lithium carbonate (10% excess), gallium oxide, aluminum oxide, iron oxide, beryllium oxide, zinc oxide, lanthanum oxide, and zirconium oxide were weighed respectively, placed in a zirconium oxide ball mill, and ball milled using isopropanol as a solvent. The mass ratio of powder to zirconium oxide ball milling beads and solvent was 1:1:10, the ball milling speed was 250 r / min, and the ball milling time was 12 h; (2) drying the ball-milled powder slurry in a 120° C. forced air drying oven for 6 h; (3) The dried powder was placed in an alumina crucible and calcined in a muffle furnace at a temperature of 900 °C for 12 h at a heating rate of 5 °C / min.
[0071] (4) The calcined powder is ground with a mortar and sieved with 200 mesh, 400 mesh, and 500 mesh sieves in turn. The purpose of sieving is to obtain fine and uniform powder particles. Weigh 150g of the sieved powder and place it in a graphite mold for dry pressing. Then transfer it to a hot press furnace filled with Ar and sinter it at 1000℃ for 40min. The pressure is 20MPa and the heating rate is 3℃ / min. After sintering, it is slowly cooled to room temperature at a rate of 2℃ / min. The sintered electrolyte sheet is cut and processed according to the needs to obtain the final required 5mm×5mm×1mm square ceramic sheet. Its XRD spectrum is as follows Figure 4 shown.
[0072] Example 4: Li 6.4 Ga 0.1 Al 0.1 La3Zr2O 12 Preparation.
[0073] (1) According to the stoichiometric ratio, lithium carbonate (10% excess), gallium oxide, aluminum oxide, lanthanum oxide, and zirconium oxide were weighed respectively, placed in a zirconium oxide ball mill, and ball milled using isopropanol as a solvent. The mass ratio of powder to zirconium oxide ball milling beads and solvent was 1:1:10, the ball milling speed was 300 r / min, and the ball milling time was 10 h; (2) drying the ball-milled powder slurry in a 120° C. forced air drying oven for 6 h; (3) The dried powder was placed in an alumina crucible and calcined in a muffle furnace at a temperature of 950°C for 12 h at a heating rate of 5°C / min.
[0074] (4) The calcined powder is ground with a mortar and sieved with 200 mesh, 400 mesh, and 500 mesh sieves in turn. The purpose of sieving is to obtain fine and uniform powder particles. Weigh 150g of the sieved powder and place it in a graphite mold for dry pressing. Then transfer it to a hot press furnace filled with Ar and sinter it at 1100℃ for 30min. The pressure is 15MPa and the heating rate is 3℃ / min. After sintering, it is slowly cooled to room temperature at a rate of 2℃ / min. The sintered electrolyte sheet is cut and processed according to the needs to obtain the final required 5mm×5mm×1mm square ceramic sheet. Its XRD spectrum is as follows Figure 5 shown.
[0075] Example 5: Li 6.6 Ga 0.05 Al 0.05 Zn 0.05 La3Zr2O 12 Preparation.
[0076] (1) According to the stoichiometric ratio, lithium carbonate (10% excess), gallium oxide, aluminum oxide, zinc oxide, lanthanum oxide, and zirconium oxide were weighed respectively, placed in a zirconium oxide ball mill, and ball milled using isopropanol as a solvent. The mass ratio of powder to zirconium oxide ball milling beads and solvent was 1:1:10, the ball milling speed was 300 r / min, and the ball milling time was 8 h; (2) drying the ball-milled powder slurry in a 120° C. forced air drying oven for 6 h; (3) The dried powder was placed in an alumina crucible and calcined in a muffle furnace at a temperature of 950 °C for 6 h at a heating rate of 5 °C / min.
[0077] (4) The calcined powder is ground with a mortar and sieved with 200 mesh, 400 mesh, and 500 mesh sieves in turn. The purpose of sieving is to obtain fine and uniform powder particles. Weigh 150g of the sieved powder and place it in a graphite mold for dry pressing. Then transfer it to a hot press furnace filled with Ar and sinter it at 1100℃ for 30min. The pressure is 15MPa and the heating rate is 3℃ / min. After sintering, it is slowly cooled to room temperature at a rate of 2℃ / min. The sintered electrolyte sheet is cut and processed according to the needs to obtain the final required 5mm×5mm×1mm square ceramic sheet. Its XRD spectrum is as follows Figure 6 shown.
[0078] Comparative Example 1: Li 6.4 Al 0.2 La3Zr2O 12 Preparation.
[0079] (1) According to the stoichiometric ratio, lithium carbonate (10% excess), aluminum oxide, lanthanum oxide, and zirconium oxide were weighed respectively, placed in a zirconium oxide ball mill, and ball milled using isopropanol as a solvent. The mass ratio of powder to zirconium oxide ball milling beads and solvent was 1:1:10, the ball milling speed was 250 r / min, and the ball milling time was 12 h; (2) drying the ball-milled powder slurry in a 120° C. forced air drying oven for 6 h; (3) The dried powder was placed in an alumina crucible and calcined in a muffle furnace at a temperature of 900 °C for 12 h at a heating rate of 5 °C / min.
[0080] (4) The calcined powder was ground in a mortar and sieved with 200-mesh, 400-mesh, and 500-mesh sieves in order to obtain fine and uniform powder particles. 1 g of the powder was weighed each time and placed in a mold with a diameter of 10 mm. The axial tablet press was used to press at a pressure of 20 MPa for 2 min to obtain a 10 mm diameter disc.
[0081] (5) A plurality of discs are sealed in a plurality of balloons, and the plurality of balloons are placed in a hydraulic press and maintained at a pressure of 20 kN for 3 min to eliminate uneven stress inside the discs.
[0082] (6) A layer of LLZO mother powder was laid on the alumina crucible, and the disc was placed on the mother powder (the purpose of laying the mother powder is to prevent lithium loss at high temperature) and covered with a thick layer of mother powder. The magnesium oxide crucible was covered on the crucible cover and sintered in a high-temperature muffle furnace at 1200℃ for 12h with a heating rate of 5℃ / min. Its XRD spectrum is shown as follows Figure 7 shown.
[0083] Experimental test: The garnet oxide solid electrolyte prepared in the above Experimental Example 1 was tested by XRD pattern and scanning electron microscope. Figure 1 The garnet structure high entropy oxide solid electrolysis Li in Example 1 6.5 Ga 0.05 Al 0.05 Zn 0.05 Be 0.05 La3Zr2O 12 The XRD pattern of Figure 1 It can be seen that its peak corresponds one-to-one with the cubic garnet phase LLZO, and there are no stray peaks. Figure 1 There are only cubic corresponding peaks but no other impurities, indicating the successful incorporation of Li elements.
[0084] Figure 2 For Li 6.5 Ga 0.05 Al 0.05 Zn 0.05 Be 0.05 La3Zr2O 12 From the scanning electron microscope photos, it can be found that the grain size is about 1-5μm, the grains are in close contact, and there are no obvious gaps or holes, indicating that it has high density.
[0085] The garnet oxide solid electrolyte prepared in the above Experimental Example 2 was tested by XRD spectrum. Figure 3 It can be seen that Figure 3 There are only cubic corresponding peaks but no other impurities, indicating the successful incorporation of Li elements.
[0086] The garnet oxide solid electrolyte prepared in the above Experimental Example 3 was tested by XRD pattern. Figure 4 It can be seen that Figure 4 There are only cubic peaks but no other impurities in the graph, indicating the successful incorporation of Li elements. Figure 5 and Figure 6 It can be seen that the Li-site elements in Examples 4 and 5 were successfully incorporated.
[0087] The garnet oxide solid electrolyte prepared in the above comparative example 1 was tested by XRD spectrum. Figure 7 It was found that there was a peak around 2θ=25°, corresponding to the LaAlO3 impurity; at the same time, it can be observed that multiple main peaks in the spectrum were split, indicating the presence of some untransformed tetragonal phase; the presence of impurities caused the LLZO lattice constant to increase, which was manifested as a shift of the peak to the left; in addition, the presence of impurities will cause the grain boundary impedance of LLZO to increase, which in turn leads to an increase in the total impedance of the material, which is ultimately manifested as a decrease in ionic conductivity.
[0088] The impedance of the embodiment and the comparative example was analyzed by EIS and calculated using the conductivity formula. The ionic conductivity of each electrolyte is summarized in Table 1.
[0089] Table 1
[0090] The difference between Examples 1 to 5 and Comparative Example 1 is that the Li site is doped with at least two elements of Fe, B, Be, Ga, Al, and Zn in equal molar numbers. As can be seen from Table 1, doping at least two elements of Fe, B, Be, Ga, Al, and Zn at the Li site can significantly improve the conductivity of the garnet-type oxide solid electrolyte.
[0091] In Example 5, the Li site is doped with three elements of Fe, B, Be, Ga, Al, and Zn in equal molar numbers. As can be seen from Table 1, the conductivity of the obtained garnet-type oxide solid electrolyte is increased by 10.7% compared with the above two elements doping. In Examples 1 to 3, the Li site is doped with at least four elements of Fe, B, Be, Ga, Al, and Zn in equal molar numbers. As can be seen from Table 1, the conductivity of the obtained garnet-type oxide solid electrolyte is increased by 42% compared with the above three elements doping, which has a surprising effect compared with the 10.7% increase in the Li site by doping with the above three elements relative to doping with two elements. Furthermore, in the present application, the Li site is doped with at least four elements of Fe, B, Be, Ga, Al, and Zn in equal molar numbers, and the stoichiometric number of Li is between 6.4 and 6.6, so that the garnet-type oxide solid electrolyte in the present application has a higher Li + The possible reason is that the Li site is doped with at least four elements of Fe, B, Be, Ga, Al, and Zn in equal molar numbers to generate a certain amount of lithium vacancies, stabilize the disordered cubic phase of LLZO, and promote Li + Ion conduction; and the incorporation of multiple elements will change the size of adjacent atoms and ionic bond energy, causing local distortion of the crystal structure and reducing Li + The migration activation energy is reduced, thereby improving the ionic conductivity; in addition, through the coordinated action of various elements, the high entropy effect unique to high entropy materials also significantly improves the phase stability of the LLZO solid electrolyte, enhances its air stability, and reduces the possibility of adverse effects of the generation of insulating Li2CO3 on ionic conductivity.
[0092] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A garnet-type oxide solid electrolyte, characterized in that: The chemical formula of the oxide solid electrolyte is Li (6.4~6.6) MLa3Zr2O 12 ; Wherein, M is a doping element, M includes at least two elements of Fe, B, Be, Ga, Al, and Zn, and the molar amount of each element in M is greater than 0 and less than or equal to 0.
1.
2. The oxide solid electrolyte according to claim 1, characterized in that M includes at least three elements of Fe, B, Be, Ga, Al, and Zn; and / or The elements in M are in equal molar ratios.
3. The oxide solid electrolyte according to claim 1 or 2, characterized in that M is selected from at least four elements of Fe, B, Be, Ga, Al, and Zn; or M includes Ga, Al, Zn, Be; or M includes Ga, Fe, Al, B; or M includes Ga, Fe, Al, Be, and Zn.
4. The oxide solid electrolyte according to claim 3, characterized in that The chemical formula of the oxide solid electrolyte is Li 6.4 Ga 0.1 Al 0.1 La3Zr2O 12、 Li 6.6 Ga 0.05 Al 0.05 Zn 0.05 La3Zr2O 12、 Li 6.5 Ga 0.05 Al 0.05 Zn 0.05 Be 0.05 La3Zr2O 12 , Li 6.4 Ga 0.05 Fe 0.05 Al 0.05 B 0.05 La3Zr2O 12 , Li 6.48 Ga 0.04 Fe 0.04 Al 0.04 Be 0.04 Zn 0.04 La3Zr2O 12 At least one of .
5. The oxide solid electrolyte according to claim 3, characterized in that The molar amount of each element in M is 0.03 to 0.
06.
6. A method for preparing a garnet-type oxide solid electrolyte, characterized in that: The preparation method comprises the following steps: Weigh a lithium source, a lanthanum source, a zirconium source and a dopant according to a stoichiometric ratio, wherein the dopant includes doping elements Fe, B, Be, Ga, Al and Zn; ball milling a mixture consisting of the lithium source, the lanthanum source, the zirconium source, the dopant and the solvent to obtain a slurry; The dried slurry is calcined at 900°C-950°C for 6h-12h, and then ground to obtain powder; Sintering the powder at a pressure of 10 MPa-20 MPa and a temperature of 1000° C.-1200° C. for 1 h-2 h to obtain an oxide solid electrolyte; Wherein, the chemical formula of the oxide solid electrolyte is Li (6.4~6.6) MLa3Zr2O 12 ; M includes at least two elements of Fe, B, Be, Ga, Al, and Zn, and the molar amount of each element in M is greater than 0 and less than or equal to 0.
1.
7. The preparation method according to claim 6, characterized in that: The sum of the masses of the lithium source, the lanthanum source, the zirconium source and the dopant is M1, the mass of the ball milling beads is M2, and the mass of the solvent is M3, then M1: M2: M3 is (1-5): (1-5): (5-20).
8. The preparation method according to claim 6, characterized in that: The ball milling speed during the ball milling process is 250r / min-400r / min; and / or The ball milling time in the ball milling process is 6h-12h.
9. The preparation method according to claim 6, characterized in that: The process of drying the slurry comprises placing the slurry in a forced air drying oven at 80° C. to 120° C. for 6 h to 12 h; and / or Before the sintering step, the preparation method further comprises sieving the milled particles through 200 mesh, 400 mesh, and 500 mesh sieves in sequence to obtain the powder; and / or Before the sintering step, the preparation method further comprises dry pressing the powder to obtain a precursor, and then hot pressing and sintering the precursor to obtain the oxide solid electrolyte.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the oxide solid electrolyte according to any one of claims 1 to 5, or the oxide solid electrolyte prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Rechargeable lithium-ion battery
US20200153038A1
Lithium-containing oxide, and method for preparing solid electrolyte
US20240239676A1
Multi-doped garnet electrolytes
WO2024035997A2
Cited By
Li-Zr double-site co-doped garnet solid electrolyte ceramic as well as preparation method and application thereof
CN120774711A